Kinetic Study on the Extraction of Copper from Aqueous Acetate Buffers with Versatic Acid 10 - 이동휘; 이화영; 임성기 (TAYLOR & FRANCIS, 1987)
The extraction rate of copper(II) from aqueous acetate buffer solutions into Versatic Acid 10 dissolved in kerosene has been investigated using a constant interfacial-area unit cell. Two alternative kinetic equations were derived under the assumption of Langmuir adsorption isotherm for the organic phase - interface distribution of extractant. Experimental results show that the overall reaction is controlled by the formation step of the second intermediate complex, CuR^HR, and that the forward extraction rate is proportional to the copper concentration in the aqueous phase, inversely proportional to the hydrogen ion concentration and proportional to a more complex function of the Versatic Acid 10 concentration. ？ 1987, Taylor & Francis Group, LLC. All rights reserved.